(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The main volume of speech use today falls on the sphere of mass communication. The concept of a single information space is of key importance for understanding the dynamics of linguistic changes, as it allows us to present the multifaceted activities of global and national mass media in the form of a single, integral system, the functioning of which has a significant impact on the course and development of linguocultural processes.